ربوٰکی قسمیں اور اس کاحکم: A Research Study of Riba, types and its Order - Qazi, Dr. Shabana; Jamal, Syed Jamal Shah (Journal of Quranic and Social Studies, 2021)
Allah Almighty created man, blessed him with life and wealth and then taught him through the prophets how to live and use wealth properly, because on the Day of Judgment he will have to give an account of all his blessings and with the rest of the blessings especially regarding wealth. The answer has to be given as to where he earned it from, what his resources were and where he spent it. Nevertheless, in the present age, such a race for wealth has started that most people do not care whether this wealth comes from halal resources or from haraam resources, but people have now given different names to haraam resources. In this regard, public interest is found in the highest interest, such as the deadly and dangerous sin, although most of the major problems and corruption in society are due to usury. The purpose is to discuss usury. This is so that everyone, especially the general public, is aware of its toxic effects, which is why this research article that’s why, we have mentioned the background of Ribbah in detail, with strong arguments from the Quran and Hadith, its prohibition so that no one has any doubt about its explicit prohibition, and finally we have clarified the difference between usury and trade which It is usually a response to a baseless objection by the liberal class.